Identifying Community/Public Health Nursing Competencies in Indonesia: A Modified Delphi Method - Widyarani, Destia; Susanto, Tantut; Wahyuni, Dwi; Pham, Huong Thi Thu (Nurse Media Journal of Nursing, 2020)
Background: Nurses in public health centers, or known as public health nurses (PHNs), have duties in implementing promotive, preventive, curative, and rehabilitative efforts. In Indonesia, there is no basic reference to the competencies that should be performed by PHNs. The provision of health services in the community should cover two areas, namely inside and outside the building (Minister of Health’s Regulation No. 279 Year 2006); it causes nurses in the community to further hone their skills while in the field.Purpose: This study aimed to identify the competencies of the Indonesian PHNs from experts using the C/PHN competencies of the Quad Council Coalition through a Delphi method.Methods: This study was quantitative research with a Delphi method. We employed a purposive sampling technique to recruit the experts of public health nurses. The experts did a Delphi method to identify, analyze, and modify the C/PHN Competencies of the Quad Council Coalition into the Indonesian version of C/PHN Competencies with local cultures.Results: Results showed that from eight domains of the Quad Council Coalition C/PHN competencies, there were changes for priority of the PHN competencies in Indonesia. All priorities were classified into eight groups, namely: (1) Leadership Skills and Thinking Systems; (2) Community Dimensions of Practice; (3) Assessment Analytic; (4) Policy Development and Program Planning; (5) Communication Skills; (6) Financial Planning and Management and Planning; (7) Public Health Sciences Skills; and (8) Cultural Competency.Conclusion: The Quad Council Coalition of C/PHN competencies are appropriate with the Indonesian PHN competencies, although the priority is changed related of local wisdom as stated in the Minister of Health’s Regulation No. 279 Year 2006. Therefore, the Indonesian P/HN competencies should be developed to support the Indonesian health people through family approach.